Knowledge, Attitudes and Practices Related to Oral Health in First-Year University Students of the Paraíso Campus of the University of Costa Rica - Barahona-Cubillo, Juan Bautista; Rojas-Brenes, Cinthya; Barboza-Solís, Cristina (Odovtos - International Journal of Dental Sciences, 2023)
People’s knowledge, attitudes, and practices related to health are built throughout life, particularly during childhood and adolescence, and they reflect the practices of their family and social circle. The aim of this study was to identify the levels of knowledge, attitudes, and practices related to oral health of first-year university students at the Paraíso Campus of the University of Costa Rica. This was done through a questionnaire of closed questions that would allow oral health educational strategies to be established in the future for this population group. For this purpose, a cross-sectional descriptive study was conducted, where 70 first-year students of the Paraíso Campus participated in the first semester of the year 2019. For data collection, a survey of 22 closed questions on knowledge, attitudes, and practices about oral health was applied, and a score on oral health knowledge was subsequently performed, based on the answers to the questions. According to the results, the level of knowledge shown about oral health is low, since the average knowledge score (7.02 points) was less than half of the maximum score (17 points). The greatest deficiency in knowledge was evidenced in topics, such as, dental biofilm, gingivitis, use of fluorides, and the role of saliva. In addition, several practices that affect the condition of the oral cavity were identified, such as harmful habits, inadequate nutrition, and poor oral hygiene habits. In this study, a general lack of knowledge was identified regarding basic concepts of oral health in young university students, who are not clear about the role of some protective or risk factors related to the main oral diseases.